Modification of the diabetes prevention program for the treatment of nonalcoholic fatty liver disease: A pilot study - Melissa Hershman; Karen Torbjornsen; Daniel Pang; Brooke Wyatt; Douglas T. Dieterich; Ponni V. Perumalswami; Andrea D. Branch; Amreen M. Dinani (Wiley, 2023)
Abstract Objective The Diabetes Prevention Program (DPP) is the gold standard lifestyle modification program that reduces incident type 2 diabetes mellitus. Patients with prediabetes and patients with non‐alcoholic fatty liver disease (NAFLD) often share metabolic features; we hypothesized that the DPP could be adapted and used to improve outcomes in patients with NAFLD. Methods NAFLD patients were recruited into a 1 year modified DPP. Demographics, medical comorbidities, and clinical laboratory values were collected at baseline, 6 and 12 months. The primary endpoint was change in weight at 12 months. Secondary endpoints were changes in hepatic steatosis, metabolic comorbidities, and liver enzymes (per‐protocol basis) and retention at 6 and 12 months. Results Fourteen NAFLD patients enrolled; three dropped out before 6 months. From baseline to 12 months, hepatic steatosis (p = 0.03), alanine aminotransferase (p = 0.02), aspartate aminotransferase (p = 0.02), high‐density lipoprotein (p = 0.01) and NAFLD fibrosis score (p < 0.001) improved, but low‐density lipoprotein worsened (p = 0.04). Conclusion Seventy‐nine percent of patients completed the modified DPP. Patients lost weight and had improvements in five out of six indicators of liver injury and lipid metabolism. Clinical Trial Registry Number NCT04988204.